Molecular Mechanisms of the Co-Evolution of Wheat and Rust Pathogens - Emmanuel N. Annan; Li Huang (Plants, 2023)
Wheat (Triticum spp.) is a cereal crop domesticated >8000 years ago and the second-most-consumed food crop nowadays. Ever since mankind has written records, cereal rust diseases have been a painful awareness in antiquity documented in the Old Testament (about 750 B.C.). The pathogen causing the wheat stem rust disease is among the first identified plant pathogens in the 1700s, suggesting that wheat and rust pathogens have co-existed for thousands of years. With advanced molecular technologies, wheat and rust genomes have been sequenced, and interactions between the host and the rust pathogens have been extensively studied at molecular levels. In this review, we summarized the research at the molecular level and organized the findings based on the pathogenesis steps of germination, penetration, haustorial formation, and colonization of the rusts to present the molecular mechanisms of the co-evolution of wheat and rust pathogens.